ORIGINAL PAPERHigh knowledge about diabetes decreases the likelihood of retinopathy in type 1 diabetic patients treated with intensive insulin therapy from the onset of the disease - Araszkiewicz, Aleksandra; Zozulińska, Dorota; Trepińska, Magdalena M.; Wierusz-Wysocka, Bogna (Archives of Medical Science, 2005)
Introduction: The aim of the study was to evaluate type 1 diabetic patients treated with intensive functional insulin therapy from the onset of the disease. Material and methods: 100 patients aged under 30 with newly diagnosed type 1 diabetes, educated in intensive insulin therapy at baseline were recruited to this single-centre clinical trial. At follow-up (5.2±1.5 years) the participants underwent a test concerning their knowledge about diabetes (20 questions). According to test results the patients were divided into three groups: group A ( 17 scores). The relationship between the patients\' knowledge and metabolic control, hsC-reactive protein and late diabetic complications was assessed. Results: At follow-up fasting plasma glucose 7.2±3.4 mmol/l, 2 hour postprandial plasma glucose 9.4±3.6 mmol/l, HbA1c 7.5±1.4%. In the knowledge test 20% reached 17 scores (mean 14.4±3.2 scores). The hsCRP level was 4.94±1.53 mg/l. We observed statistically significant differences in hsCRP concentrations between the high and low levels of knowledge groups. The level of patients\' knowledge significantly negatively correlated with hsCRP and HbA1c (r=-0.41, p<0.05 and r=-0.31, p<0.05). Background retinopathy and positive microalbuminuria were detected in 8 (9%) and 9 (10%) subjects, respectively. The risk of retinopathy was connected only with low knowledge (OR 5.67; 95% CI: 2.02-15.82, p<0.0002). Conclusions: Our study confirms intensive insulin therapy and patients\' knowledge about diabetes as a possibly beneficial treatment regimen in reducing the incidence of vascular complications in type 1 diabetes.